# Solve for y 3/4=3/(2y-4)

34=32y-4
Rewrite the equation as 32y-4=34.
32y-4=34
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
3⋅4=(2y-4)⋅3
Solve the equation for y.
Rewrite the equation as (2y-4)⋅3=3⋅4.
(2y-4)⋅3=3⋅4
Multiply 3 by 4.
(2y-4)⋅3=12
Divide each term by 3 and simplify.
Divide each term in (2y-4)⋅3=12 by 3.
(2y-4)⋅33=123
Cancel the common factor of 3.
Cancel the common factor.
(2y-4)⋅33=123
Divide 2y-4 by 1.
2y-4=123
2y-4=123
Divide 12 by 3.
2y-4=4
2y-4=4
Move all terms not containing y to the right side of the equation.
Add 4 to both sides of the equation.
2y=4+4
2y=8
2y=8
Divide each term by 2 and simplify.
Divide each term in 2y=8 by 2.
2y2=82
Cancel the common factor of 2.
Cancel the common factor.
2y2=82
Divide y by 1.
y=82
y=82
Divide 8 by 2.
y=4
y=4
y=4
Solve for y 3/4=3/(2y-4)

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top